Remix as Professional Learning: Educators' Iterative Literacy Practice in CLMOOC - Anna Smith; Stephanie West-Puckett; Christina Cantrill; Mia Zamora (MDPI AG, 2016)
The Connected Learning Massive Open Online Collaboration (CLMOOC) is an online professional development experience designed as an openly networked, production-centered, participatory learning collaboration for educators. Addressing the paucity of research that investigates learning processes in MOOC experiences, this paper examines the situated literacy practices that emerged as educators in CLMOOC composed, collaborated, and distributed multimediated artifacts. Using a collaborative, interactive visual mapping tool as participant-researchers, we analyzed relationships between publically available artifacts and posts generated in one week through a transliteracies framework. Culled data included posts on Twitter (n = 678), a Google+ Community (n = 105), a Facebook Group (n = 19), a blog feed (n = 5), and a "make" repository (n = 21). Remix was found to be a primary form of interaction and mediator of learning. Participants not only iterated on each others' artifacts, but on social processes and shared practices as well. Our analysis illuminated four distinct remix mobilities and relational tendencies-bursting, drifting, leveraging, and turning. Bursting and drifting characterize the paces and proximities of remixing while leveraging and turning are activities more obviously disruptive of social processes and power hierarchies. These mobilities and tendencies revealed remix as an emergent, iterative, collaborative, critical practice with transformative possibilities for openly networked web-mediated professional learning.